Conceptualization of the Relationship between Brand Equity and Purchase Behavior - Ogunnaike, Olaleke Olusye; Kehinde, Oladele Joseph; Omoyayi, Oluwadamilola Oluwatosin; Popoola, Oluwamakinde Oluwamayowa; Amoruwa, Andrew (International Review of Management and Marketing, 2017)
Assessing the customer perspective of brand equity will provide deep understanding of how brands influence purchase behaviour of customers. The purpose of this paper is to formulate a conceptual framework that will provide an understanding of the relationship existing between the elements of brand equity and that of purchase behaviour. The adoption of Aaker’s brand equity model will serve as a guide for conceiving associations between brand equity and purchase behaviour for this study. Literatures within the area of brand equity and purchase behaviour will be reviewed in order to develop the conceptual framework on the elements of brand equity and purchase behaviour. Keywords: Brand equity, purchasing behaviour, customers JEL Classifications: C91, M3